Analysis of the Influence of Tax Service, Tax Advertising, and Zakat Policy as a Reduction of Taxable Income to Tax Paying Compliance for Individual Taxpayers in the Tax Service Office Pratama Sawangan, Depok, West Java - Mulyaning Wulan; Tatin Suhartini; Efri Syamsul Bahri (International Journal of Zakat, 2018)
This study aims to understand the influence of independent variables (tax service, tax advertising, and zakat policy as reduction of taxable income) on the dependent variable (taxpaying compliance). Partial test results indicate that the variables (X1) and (X2) have a positive and significant influence on tax paying compliance of Muslim individual Taxpayers. The variable significance level (X1) is 0.310, and the variable significance level (X3) is 0,506. Partial testing of advertisement variables of tax equal to 0.014, which indicates that tax advertisement partially has no positive and significant effect to Taxpayer compliance. The statistical testing revealed that the variables (X1, X2 and X3) have a positive and significant influence on the dependent variable (Y). F artihmatic of 29, 395> Ftable of 2.69 with a significance level of 0.000 <0.1 Keywords: Service, Advertising, Zakat Policy, taxable Income, Compliance